Traqueotomia na infância - Nakanishi, M. (2001)
Introduction: The airway control to supply oxigenation and hygiene of the traqueobronquical tree or support a ventilatory assistance is the basis of the treatment of respiratory failure. This control is getting by intubation or tracheotomy. Aim: The aim of this paper was discuss and analyze the history, the indications, surgical techniques and complications of the tracheotomies performed in children. Study design: retrospectial chart review. Material and method: From 1975 to 1999 were done 73 tracheotomies in children. We studied: sex, color, prematurity, age, weight, number of previous intubation, period of intubation, primary diagnostic, indication, type of the surgery, presence of orotracheal intubation during the surgery, complications, time of tracheotomy and decanulation. Results: Analyzing 73 children, 35 (47,9%) were girls and 38 (52,1%) boys. The great majority, 58 (79,5%) were bom in term and 15 (20,5%) pre-term (< 37 weeks). The mean age was four years and two months. The most frequent primary diagnostic was the pulmonary disease (32,9%) and the main indication was ventilatory support / prolonged intubation (40,3%). The pneumotorax (28,5%) and hemorrhage (22,5%) were the principal initial complication and the subglotic stenosis (71,4%) the most frequent late complication. Conclusion: The tracheotomy is a usual procedure in pediatrics ICU associated to prolonged ventilatory support. Although the high morbidity in new birth with low weight and lactents due to surgical technique and primary disease (broncopneumonias) it is declining with intensive training of the parents, medical and nurse group, beyond the material improvement.